Synthesis of Highly Stabilized Phosphorus Ylides from Acetylenic Esters, CH-acids and Triphenylphosphine in Aqueous Media - Ramazani, Ali; Dolatyari, Leila; Reza Kazemizadeh, Ali; Ahmadi, Ebrahim (Asian Journal of Chemistry, 2016)
Protonation of the highly reactive 1:1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by CH-acids (nitromethane, acetylacetone, dibenzoylmethane and diethyl malonate) leads to vinyl triphenylphosphonium salts, which undergo Michael addition reaction with conjugate base to produce corresponding highly stabilized phosphorus ylides in the mixture of acetone-water (2:1).